2006
DOI: 10.1007/s10686-006-9057-y
|View full text |Cite
|
Sign up to set email alerts
|

The INTEGRAL – HESS/MAGIC connection: A new class of cosmic high energy accelerators from keV to TeV

Abstract: The recent completion and operation of the High Energy Stereoscopic System [1], an array of ground based imaging Cherenkov telescopes, has provided a survey with unprecedented sensitivity of the inner part of the Galaxy and revealed a new population of very high energy gamma-rays sources emitting at E>100 GeV. Most of them were reported to have no known radio or X-ray counterpart and hypothesised to be representative of a new class of dark nucleonic cosmic sources. In fact, very high energy gammarays with ener… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 16 publications
(39 reference statements)
0
1
0
Order By: Relevance
“…In fact, high energy gamma-rays with energies E > 10 11 eV were, and actually are, the best proof of non-thermal processes in the universe and provide a direct in-site view of matter-radiation interaction at energies by far greater than producible in human-made accelerators. INTE-GRAL survey results were a powerful tool to immediately investigate the nature of this new type of galactic cosmic accelerator (Ubertini, 2005) thanks to the unprecedented INTE-GRAL/IBIS angular resolution and Point Source Location Capability of about 1-2 arcminute between 15 keV and a few MeV. Furthermore, INTEGRAL had already performed deep observations of almost all HESS detected sources: the new IN-TEGRAL source IGR J18135−1751 was identified as the soft gamma-ray counterpart of HESS J1813−178 (Ubertini et al, 2005) and AX J1838.0−0655 as the X/gamma-ray counterpart of HESS J1837−069 (Malizia et al, 2005), as shown in Fig.…”
Section: Brief Overview Of Integral Surveysmentioning
confidence: 99%
“…In fact, high energy gamma-rays with energies E > 10 11 eV were, and actually are, the best proof of non-thermal processes in the universe and provide a direct in-site view of matter-radiation interaction at energies by far greater than producible in human-made accelerators. INTE-GRAL survey results were a powerful tool to immediately investigate the nature of this new type of galactic cosmic accelerator (Ubertini, 2005) thanks to the unprecedented INTE-GRAL/IBIS angular resolution and Point Source Location Capability of about 1-2 arcminute between 15 keV and a few MeV. Furthermore, INTEGRAL had already performed deep observations of almost all HESS detected sources: the new IN-TEGRAL source IGR J18135−1751 was identified as the soft gamma-ray counterpart of HESS J1813−178 (Ubertini et al, 2005) and AX J1838.0−0655 as the X/gamma-ray counterpart of HESS J1837−069 (Malizia et al, 2005), as shown in Fig.…”
Section: Brief Overview Of Integral Surveysmentioning
confidence: 99%